2005
DOI: 10.1039/b510159j
|View full text |Cite
|
Sign up to set email alerts
|

Escape from the interferon response associated with RNA interference using vectors that encode long modified hairpin-RNA

Abstract: In mammalian cells, siRNAs have been used to induce RNA interference (RNAi) in an attempt to prevent nonspecific effects (including the interferon (IFN) response) which are caused by long double-stranded RNAs (dsRNAs) of more than 30 bp. In this report, we describe a novel and simple strategy for avoiding activation of the IFN response by dsRNA. We show that modified hairpin-RNAs (mhRNAs) of more than 100 bp, with multiple specific point-mutations within the sense strand and transcribed from the U6 or tRNA(Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 37 publications
3
46
0
1
Order By: Relevance
“…A similar result has recently been described in literature. 33,66 Exposure of cells to a 50 bp in vitro synthesized dsRNA induces the production of class I IFNs, but not when such molecules are expressed in the cell from a DNA construct with the U6 promoter. Modification of lhRNAs expressed from a Pol III promoter by inclusion of multiple G:U wobbles induced RNAi without any non-specific effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result has recently been described in literature. 33,66 Exposure of cells to a 50 bp in vitro synthesized dsRNA induces the production of class I IFNs, but not when such molecules are expressed in the cell from a DNA construct with the U6 promoter. Modification of lhRNAs expressed from a Pol III promoter by inclusion of multiple G:U wobbles induced RNAi without any non-specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of lhRNAs expressed from a Pol III promoter by inclusion of multiple G:U wobbles induced RNAi without any non-specific effects. 66 In fact, most reports on IFN induction by long dsRNAs in mammalian cells are based on transfection of cells with in vitro synthesized dsRNAs. 40,67 Apparently, endogenously produced dsRNA is less active than exogenous dsRNA in inducing the IFN response.…”
Section: Discussionmentioning
confidence: 99%
“…Long-hairpin RNAs (lhRNAs) greater than 50 bp in length can be expressed in cells and create multiple siRNAs via Dicer-mediated processing. [43][44][45] Expressed lhRNAs have been shown to be effective in cell culture against targets for HCV 46 and HIV 38,47,48 and in an in vivo murine hydrodynamic injection model of HBV replication for targets against HBV. 44 However, processing and knockdown efficacy of these substrates is asymmetric, being greatest at the base of the hairpin and tapering-off across the full length of the duplex.…”
Section: Multi-targeting Rnai Approaches To Inhibit Hiv Replicationmentioning
confidence: 99%
“…However, we have recently shown that endogenously (nuclear) expressed shRNAs evade detection by TLRs, RIG-1 and PKR when integrated in CD34+ progenitor hematopoietic stem cells. 56 The expression of lhRNAs (430 bp) also appears to be well tolerated and does not induce IFN gene activation, whether transiently expressed in cells 43,45,48 or in vivo when injected in mice by hydrodynamic tail-vein injection. 44 These results suggest that expressed dsRNAs may mimic nuclear-derived natural RNAi precursors and augurs well for future gene therapy clinical trials.…”
Section: Multi-targeting Rnai Approaches To Inhibit Hiv Replicationmentioning
confidence: 99%
“…In this sense, several groups have shown that HIV-1-specific long hairpin (lhRNA) or long dsRNA endogenously expressed can inhibit HIV-1 replication without induction of IFN response [115][116][117][118]. More recently, Konstnatinova and coworkers reported a potent trans-inhibition of HIV replication using an HIV-1 variant with a 300pb-lhRNA at the 3 0 genome position of the nef gene [119].…”
Section: Rnai As a New Tool Against Hiv-1mentioning
confidence: 99%